Long-term consequences of Bti applications on aquatic insect emergence: Insights from a 4-year mesocosm study - Agnes Schöndorfer; Sara Kolbenschlag; Peer Bauspiess; Jens Schirmel; Eric Bollinger; Alessandro Manfrin; Mirco Bundschuh (Ecotoxicology and Environmental Safety)
Aquatic biomass and essential nutrients can subsidize terrestrial food webs. However, stressors in the aquatic ecosystem, such as the non-chemical mosquito control agent Bti (Bacillus thuringiensis israelensis), may affect such subsidies by changing the dynamics and diversity of emergent aquatic insects. Such changes in emergence phenology may influence riparian predators with consequences for the terrestrial food web. Here we asked whether repeated Bti application over four consecutive vegetative periods cause similar impacts over these years (i.e., 2020–2023). We used floodplain pond mesocosms and measured insect emergence from control and Bti-treated ponds between April and August in each year. We found significant effects on insect emergence dynamics and community composition only during the first year. This effect disappeared over the three following years. Our observations suggest a shift in community composition, for example, by replacing more Bti-sensitive (i.e., Chironomidae) with more tolerant insect species – a hypothesis that is partially supported by changes in the wider community of emergent aquatic insects during the study. Alternatively, a reduced Bti activity could explain this pattern: The activity could be affected by changes in environmental factors such as the accumulation of organic carbon and fine sediment. All in all, our data point to a higher annual variability in insect emergence dynamics and the community of emergent aquatic insects relative to the impacts caused by Bti.